Infectivity studies of Leishmania (Leishmania) infantum chagasi isolated from non-ulcerated cutaneous leishmaniasis - Araujo Flores, Gabriela Venicia; Sandoval Pacheco, Carmen Maria; Tomokane, Thaise Yumie; Sosa Ochoa, Wilfredo Humberto; Silveira, Fernando Tobias; Zúniga, Concepción; Pereira Corbett, Carlos Eduardo; Soares, Rodrigo Pedro Pinto; Passero, Luiz Felipe Domingues [UNESP]; Laurenti, Marcia Dalastra (Instituto de Medicina Tropical, 2025)
In Honduras, Leishmania (Leishmania) infantum chagasi, the etiological agent of visceral leishmaniasis (VL), is responsible for non-ulcerated cutaneous leishmaniasis (NUCL). We characterized NUCL and VL Honduran strains to understand intraspecies infectivity. Based on in-vitro assays, we aimed to elucidate certain host-parasite interactions in VL and NUCL isolates through a hamster model. To assess the capacity of these strains to infect peritoneal macrophages, we exposed them to promastigotes from NUCL and VL patients at varying temperatures and time intervals (32, 34, and 36 °C; 24 and 48 h) and infection-index (II) was determined. No significant differences were observed over time for dermotropic strains; however, a higher II was noted at lower temperatures (32 and 34 °C). Interestingly, only the VL strain exhibited a higher II at elevated temperatures (34 and 36 °C) at 48 h. Low levels of oxygen and nitrogen-derived metabolites were detected in both NUCL and VL strains. For in-vivo assays, hamsters were infected subcutaneously (SC) and intraperitoneally (IP) with 107-promastigotes from NUCL and VL patients. After 90 days of infection, parasite-load and histopathological changes were assessed from spleen samples. Regardless of the administration route, no substantial differences were observed in the histopathological features between NUCL and VL strains. In conclusion, lower temperatures may favor parasite infection for NUCL strains, mirroring conditions found in the skin. This contrasts with the VL strain, which demonstrated a superior II at higher temperatures, a condition normally found in the viscera. Our data also indicate that M. auratus is susceptible to Honduran L. (L.) infantum chagasi strains, circumventing the skin barrier by IP or SC injection.
Keywords: Non-ulcerated cutaneous leishmaniasis; Leishmania (Leishmania) infantum chagasi; Infectivity; Experimental infection; Hamster